2005
DOI: 10.1021/jm0408621
|View full text |Cite
|
Sign up to set email alerts
|

4-Benzyl and 4-Benzoyl-3-dimethylaminopyridin-2(1H)-ones:  In Vitro Evaluation of New C-3-Amino-Substituted and C-5,6-Alkyl-Substituted Analogues against Clinically Important HIV Mutant Strains

Abstract: In a program to optimize the anti-HIV activity of the 4-benzyl and 4-benzoyl-3-dimethylaminopyridinones 9 and 10, lead compounds in a new class of highly potent non-nucleoside type inhibitors of HIV-1 reverse transcriptase, modification of the alkyl substitutents at the C-5 and C-6 positions on the pyridinone ring and of the substitutents on the C-3 amino group has been studied. Of the 17 new 5/6-modified analogues prepared, compounds 31b and 32b substituted at C-5 by an extended nonpolar chain containing an e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
69
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(71 citation statements)
references
References 34 publications
2
69
0
Order By: Relevance
“…F227C was the dominant mutation selected by MK-4965 in subtype A and C viruses but was not found in the BTV from subtype B viruses during resistance selection with the three compounds, despite the fact that the mutation confers significant resistance to EFV and ETV in subtype B viruses (7,26). Although the phenylalanine codon (TTC) at position 227 in the RT from subtype B viruses is different from that of subtype A and C viruses (TTT), the mutation from phenylalanine to cysteine (TGT or TGC) requires only a single base change for all three subtype viruses.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…F227C was the dominant mutation selected by MK-4965 in subtype A and C viruses but was not found in the BTV from subtype B viruses during resistance selection with the three compounds, despite the fact that the mutation confers significant resistance to EFV and ETV in subtype B viruses (7,26). Although the phenylalanine codon (TTC) at position 227 in the RT from subtype B viruses is different from that of subtype A and C viruses (TTT), the mutation from phenylalanine to cysteine (TGT or TGC) requires only a single base change for all three subtype viruses.…”
Section: Discussionmentioning
confidence: 92%
“…However, even though the replication capacity of viruses with the Y188L mutation is reportedly comparable to that of viruses containing the K103N mutation (6), Y188L was not selected by MK-4965 and is present in only ϳ5% of patients who experience virologic failure in therapy with EFV-containing regimens (35). The potential reason for the rare emergence of the Y188L mutation may be the need for two base changes in order to convert tyrosine to leucine (7). The Y188L mutation is derived from an intermediate mutant, possessing either the Y188H or the Y188F mutation.…”
Section: Discussionmentioning
confidence: 99%
“…8 Despite several studies pointing out compound flexibility as an important parameter for conserving potency on various mutant viral strains, the pyridinone compounds previously described only include arylthio, aryloxy, or benzyl moieties at position 4 of the pyridinone ring. 9,10 We now report in this study the design, synthesis, and HIV-1 inhibiting properties of a new series of potent 4-cycloalkyloxypyridin-2(1H)-one derivatives ( Figure 2). Optimization of this series led to the identification of compounds combining high potency against wild-type HIV-1 and a panel of single and double mutant strains with very low cytotoxicity.…”
Section: Introductionmentioning
confidence: 99%
“…This has led to suggest the importance of sulfonyl and amine moieties for the activity. In this milieu to explore the scope of chemical space of 4-benzyl/benzoyl-3-dimethylaminopyridin-2(1H)-ones ( Figure 1C; Table 1) 16 as HIV-1 RT inhibitors, an attempt has made to rationalize their activity with 0D-2D descriptors from DRAGON software 17 . Feature selection procedures are essential components of modeling studies wherever the number of descriptors involved is very large.…”
Section: Research Articlementioning
confidence: 99%
“…In these analogues, the negative coefficient of LogP may be viewed as favorability of hydrophilic or polar compounds for better activity. The earlier modeling study on these analogues has suggested that -NH-CO-portion of pyridinone moiety offers polar interactions with the receptor 16,39 . This may be satisfying one polar interaction site of the enzyme.…”
Section: G5mentioning
confidence: 99%